2020
DOI: 10.1186/s10020-020-00152-8
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin suppresses NEAT1 and Akt signaling in treating paclitaxel-resistant non-small cell of lung cancer

Abstract: Background: The development of paclitaxel-resistance led to the tumor relapse and treatment failure of non-small cell lung cancer. Shikonin has been demonstrated to show anti-cancer activity in many cancer types. The present study aimed to investigate the anti-cancer activity of shikonin in paclitaxel-resistant non-small cell lung cancer treatment. Methods: MTT, clonogenic assay, apoptotic cell death analysis, western blot, qRT-PCR, gene knockdown and overexpression, xenograft experiment, immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In fact, several studies on NEAT1 lncRNA have shown that upregulated NEAT1 facilitated tumor cell viability, invasion, and migration in breast cancer 32 . In Non-small-cell lung carcinoma, Shikonin mediated NEAT1 suppression resulted in apoptotic cell death of paclitaxel-resistant cell lines 33 . In another study, lncRNA NEAT1 was shown to facilitate the progression of gallbladder cancer via the upregulation of Survivin expression, suggesting its potential use as a biomarker in gallbladder cancer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies on NEAT1 lncRNA have shown that upregulated NEAT1 facilitated tumor cell viability, invasion, and migration in breast cancer 32 . In Non-small-cell lung carcinoma, Shikonin mediated NEAT1 suppression resulted in apoptotic cell death of paclitaxel-resistant cell lines 33 . In another study, lncRNA NEAT1 was shown to facilitate the progression of gallbladder cancer via the upregulation of Survivin expression, suggesting its potential use as a biomarker in gallbladder cancer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin was demonstrated to suppress proliferation and induce cell cycle arrest in human colon cancer through inhibiting hypoxia-inducible factor-1 alpha signaling both in vitro and vivo 4 . Shikonin induced apoptosis of paclitaxel-resistant non-small cell lung cancer (NSCLC) cell lines and xenograft tumors through suppressing NEAT1 and Akt signaling 5 . Recently, Shikonin was reported to impede biosynthetic pathways critical for leukemia cell survival by the combination of dimethylaminoparthenolide 6 .…”
Section: Introductionmentioning
confidence: 99%
“…apoptosis of paclitaxel-resistant non-small cell lung cancer (NSCLC) cell lines and xenograft tumors through suppressing NEAT1 and Akt signaling 5 . Recently, Shikonin was reported to impede biosynthetic pathways critical for leukemia cell survival by the combination of dimethylaminoparthenolide 6 .…”
mentioning
confidence: 99%
“…MALAT1 and NEAT1 have been widely studied non-coding RNAs, and some studies have demonstrated that they have clear correlations with various cancers such as hepatocellular carcinoma and lung cancer [ 30 33 ]. It has also been reported that MALAT1 can be used as ceRNA of miR-199a to promote the expression of ZHX1 , which in turn can regulate the proliferation of GBM cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%